2017
DOI: 10.1101/144204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the use of the experimentally determined enzyme inhibition constant as a measure of absolute binding affinity

Abstract: Defined as a state function representing an inhibitor's absolute affinity for its target enzyme, the experimentally determined enzyme inhibition constant (K i ) is widely used to rank order binding affinities of different inhibitors for a common enzyme or different enzymes for a common inhibitor and to benchmark computational approaches to predicting binding affinity. Herein, we report that adsorption of bis (7)-tacrine to the glass container surface increased its K i against Electrophorus electricus acetylcho… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…The result indicated that 4‐HR showed the most effectiveness in inhibiting PPO from Pacific white shrimp cephalothorax under the experimental conditions. The K i value, also known as inhibitor dissociation constant, is an equilibrium constant of a reversible inhibitor to form a complex with its target enzyme (Darras & Pang, ). It is widely used as an indicator for the degree of enzyme inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…The result indicated that 4‐HR showed the most effectiveness in inhibiting PPO from Pacific white shrimp cephalothorax under the experimental conditions. The K i value, also known as inhibitor dissociation constant, is an equilibrium constant of a reversible inhibitor to form a complex with its target enzyme (Darras & Pang, ). It is widely used as an indicator for the degree of enzyme inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…The values of IC 50 and K i for the three enzymes were <5 μM. The K i represents the absolute affinity of an inhibitor for its target enzyme and lower K i value means stronger inhibitory effect of inhibitor against the target enzyme (Darras & Pang, 2017 Gourieux, & Bilbault, 2016). In addition, a case reported that rhabdomyolysis was caused by the moderate CYP3A4 inhibitor fluconazole in a patient on stable atorvastatin therapy (Hsiao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The values of IC 50 and K i for the three enzymes were <5 μ m . The K i represents the absolute affinity of an inhibitor for its target enzyme and lower K i value means stronger inhibitory effect of inhibitor against the target enzyme (Darras & Pang, ). Data fitting using Dixon and Lineweaver–Burk plots demonstrated the competitive inhibition of artocarpin against CYP3A4 and noncompetitive inhibition against UGT1A3 and UGT1A7.…”
Section: Discussionmentioning
confidence: 99%
“…K i reflects the affinity of an inhibitor for its target enzyme, and the lower the K i , the stronger the inhibitory effect on the target enzyme. 32 DDI was therefore possible when auriculasin was coadminstrated with CYP3A4 substrates (e.g., ibrutinib and atorvastatin), 33,34 CYP2C9 substrates (e.g., warfarin and phenytoin), 35 or UGT1A8 substrates (e.g., raloxifene). 36 Molecular docking was used to explore the molecular mechanism of interactions between auriculasin and CYPs.…”
Section: ■ Discussionmentioning
confidence: 99%